2020
DOI: 10.1021/acs.jafc.0c04459
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Hydrolysate Corrects Anemia in Chronic Kidney Disease via Anti-Inflammatory Renoprotection and HIF-2α-Dependent Erythropoietin and Hepcidin Regulation

Abstract: Anemia is a common chronic kidney disease (CKD) complication contributing to increased morbidity and mortality. Collagen-based traditional Chinese nutraceuticals have long been used in antianemic therapies. This study aims to investigate the therapeutic effectiveness of porcine collagen hydrolysate (CH) and its underlying mechanism in the treatment of renal anemia by using adenine-induced CKD mice, RAW264.7 macrophages, and HepG2 hepatoma cells, with prolyl-hydroxyproline as a reference compound for collagen-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To validate whether collagen peptides could stimulate intestinal nonheme iron absorption in vivo, CH and Pro-Hyp were orally administered to female rats with the duodenal gene transcriptional levels of Dcytb, DMT1, FPN, and HEPH measured at 2 h post-dose, a time point chosen to exclude the possibility that their effects on duodenal gene expression were secondary to their regulation of systemic erythropoietin and hepcidin production according to previous studies. , As shown in Figure a,b, CH and Pro-Hyp induced significantly increased the duodenal gene transcription levels of Dcytb, DMT1, FPN, and HEPH in rats in a dose-dependent manner, confirming direct stimulation of intestinal nonheme iron absorption by collagen peptides in vivo. According to the western blotting results (Figure c,d), the CH and Pro-Hyp dose-dependently increased the duodenal protein level of HIF-2α in rats, validating the activation of HIF-2α signaling by collagen peptides in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate whether collagen peptides could stimulate intestinal nonheme iron absorption in vivo, CH and Pro-Hyp were orally administered to female rats with the duodenal gene transcriptional levels of Dcytb, DMT1, FPN, and HEPH measured at 2 h post-dose, a time point chosen to exclude the possibility that their effects on duodenal gene expression were secondary to their regulation of systemic erythropoietin and hepcidin production according to previous studies. , As shown in Figure a,b, CH and Pro-Hyp induced significantly increased the duodenal gene transcription levels of Dcytb, DMT1, FPN, and HEPH in rats in a dose-dependent manner, confirming direct stimulation of intestinal nonheme iron absorption by collagen peptides in vivo. According to the western blotting results (Figure c,d), the CH and Pro-Hyp dose-dependently increased the duodenal protein level of HIF-2α in rats, validating the activation of HIF-2α signaling by collagen peptides in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Our recent studies revealed the HCP-dependent correction of anemia associated with iron deficiency and chronic kidney disease by dietary collagen via the HIF-2α-mediated regulation of erythropoietin and hepcidin production. 19,20 We hypothesize that HCPs may serve as PHD inhibitors to activate the HIF-2α signaling pathway. The present study observed the effects of collagen peptides to stimulate intestinal nonheme iron absorption by HIF-2α-dependent upregulation of Dcytb, DMT1, FPN, and HEPH in polarized Caco-2 cell monolayers and characterized the PHD inhibiting activity of HCPs by using recombinant human PHD3 protein and molecular docking analysis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are the cytokines that may reduce the use of iron reserves from reticuloendothelial cells and may prevent the kidney from producing EPO. Additionally, they directly suppress the growth of erythroid precursor cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study that interferes with PHD2 [ 24 ], the stability of HIF is upregulated, and the erythrocyte pressure ratio level and EPO of mice are both markedly elevated. In the progression of CKD to end-stage renal disease (ESRD), peritubular interstitial fibroblasts differentiate into myofibroblasts, and renal EPO production capacity turns down [ 25 ]. Nevertheless, failure of PHD protein is able to restore the expression of EPO gene in the impaired kidney.…”
Section: Mechanism Of Hif Regulating Anemia In Ckdmentioning
confidence: 99%